2012
DOI: 10.1210/jc.2011-2291
|View full text |Cite
|
Sign up to set email alerts
|

Germline AIP Mutations in Apparently Sporadic Pituitary Adenomas: Prevalence in a Prospective Single-Center Cohort of 443 Patients

Abstract: This large prospective cohort study confirms the very low prevalence of germline AIP mutations in patients with apparently sporadic pituitary adenomas. We propose to limit AIP testing to patients diagnosed before age 40 yr with apparently sporadic large pituitary adenomas, especially GH- or PRL-secreting adenomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
131
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 163 publications
(148 citation statements)
references
References 21 publications
13
131
2
2
Order By: Relevance
“…A long prospective study is clearly required to assess the impact of AIP screening in family members of AIPmut patients in order to clarify the natural history of asymptomatic AIPmut carriers. In mutation-negative patients, we did not identify any large genomic deletion of AIP by MLPA in agreement with three other previous studies (6,7,11). This molecular abnormality could account for 9.5% of AIPnegative FIPA kindreds (30), and among 64 unrelated patients from a FIPA cohort of our laboratory, we identified one family member of homogenous FIPA with acromegaly, with large genomic deletion of AIP in exon 1 (A Barlier, personal communication).…”
Section: Marker Genomic Positionsupporting
confidence: 92%
See 4 more Smart Citations
“…A long prospective study is clearly required to assess the impact of AIP screening in family members of AIPmut patients in order to clarify the natural history of asymptomatic AIPmut carriers. In mutation-negative patients, we did not identify any large genomic deletion of AIP by MLPA in agreement with three other previous studies (6,7,11). This molecular abnormality could account for 9.5% of AIPnegative FIPA kindreds (30), and among 64 unrelated patients from a FIPA cohort of our laboratory, we identified one family member of homogenous FIPA with acromegaly, with large genomic deletion of AIP in exon 1 (A Barlier, personal communication).…”
Section: Marker Genomic Positionsupporting
confidence: 92%
“…Indeed, in our study, the positive genetic screening in the three family members was not accompanied by the identification of any PA on MRI. In five AIPmut carriers from the study of Cazabat et al (7), no adenoma was identified by MRI, and of the AIPmut carriers (nZ2/21) from the study conducted by Tichomirowa et al (11), two family members (not included in the current study) were diagnosed with a microadenoma and without associated hormonal oversecretion. Whether there are specific AIP mutants associated with higher penetrance of the disease (34) and (35).…”
Section: Marker Genomic Positionmentioning
confidence: 72%
See 3 more Smart Citations